1999
DOI: 10.1103/physrevb.60.16762
|View full text |Cite
|
Sign up to set email alerts
|

Theory of magnetoacoustic transport in modulated quantum Hall systems nearν=1/2

Abstract: Motivated by the experimental results of Willett et al [Phys.Rev. Lett. 78, 4478 (1997)] we develop a magnetotransport theory for the response of a two-dimensional electron gas (2DEG) in the fractional quantum Hall regime near Landau level filling factor ν = 1/2 to the surface acoustic wave (SAW) in the presence of an added periodic density modulation. We assume there exists a composite fermion Fermi surface (CF-FS) at ν = 1/2, and we show that the deformation of the circular CF-FS due to the density modulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Likewise, the flattening points at the FS may give rise to some anomalies in the magnetoacoustic response of a two-dimensional electron gas, as shown in the papers [9,10].…”
Section: Introductionmentioning
confidence: 88%
“…Likewise, the flattening points at the FS may give rise to some anomalies in the magnetoacoustic response of a two-dimensional electron gas, as shown in the papers [9,10].…”
Section: Introductionmentioning
confidence: 88%
“…Some recent experiments have shown that variation of density in two-dimensional electron systems lead to a fictitious periodic magnetic field [5] and a geometric resonance of the classical cyclotron orbit and the field period. A theory of this effect has been lately proposed Zimbovskaya and Birman [6].…”
Section: Introductionmentioning
confidence: 99%
“…To get a suitable approximation for the CF conductivity we start from the standard solution of the Boltzmann transport equation for the CF distribution function. This gives us the following results for the CF conductivity components for a single layer [9]:…”
mentioning
confidence: 99%